Two functionally distinct subsites for the binding of internal blockers to the pore of voltage-activated K(+) channels - Baukrowitz, Thomas (The National Academy of Sciences of the USA, 1996)
Many blockers of Na(+) and K(+) channels act by blocking the pore from the intracellular side. For Shaker K(+) channels, such intracellular blockers vary in their functional effect on slow (C-type) inactivation: Some blockers interfere with C-type inactivation, whereas others do not. These functional differences can be explained by supposing that there are two overlapping “subsites” for blocker binding, only one of which inhibits C-type inactivation through an allosteric effect. We find that the ability to bind to these subsites depends on specific structural characteristics of the blockers, and correlates with the effect of mutations in two distinct regions of the channel protein. These interactions are important because they affect the ability of blockers to produce use-dependent inhibition.